2018
DOI: 10.3904/kjim.2016.165
|View full text |Cite
|
Sign up to set email alerts
|

Depth and combined infection is important predictor of lower extremity amputations in hospitalized diabetic foot ulcer patients

Abstract: Background/AimsAs the prevalence of diabetes mellitus and its complications increase rapidly, diabetic foot ulcers (DFUs), which are a major diabetic complication, are expected to increase. For prevention and effective treatment, it is important to understand the clinical course of DFUs. The aim of this study was to investigate the natural course and predictors of amputation in patients with DFUs who required hospitalizationMethodsA total of 209 patients with type 2 diabetes, aged 30 to 85 years, who visited e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…It had been suggested that this condition can be prevented by wearing proper footwear, maintaining hygiene, and performing daily physical examination. 4 But this is inconsistent to the studies conducted in: Saudi Arabia, with a cross-sectional study that states neuropathy was not significantly associated with the development of diabetic foot ulcer, 15 and Arbaminch Hospital, Ethiopia, with a cross-sectional study design which states that neuropathy was not significantly associated with the development of diabetic foot ulcer. 7 The possible reason for this discrepancy could be due to differences in the duration of diabetes mellitus that the patient has had.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It had been suggested that this condition can be prevented by wearing proper footwear, maintaining hygiene, and performing daily physical examination. 4 But this is inconsistent to the studies conducted in: Saudi Arabia, with a cross-sectional study that states neuropathy was not significantly associated with the development of diabetic foot ulcer, 15 and Arbaminch Hospital, Ethiopia, with a cross-sectional study design which states that neuropathy was not significantly associated with the development of diabetic foot ulcer. 7 The possible reason for this discrepancy could be due to differences in the duration of diabetes mellitus that the patient has had.…”
Section: Discussionmentioning
confidence: 91%
“…These were significant factors for the development of DFU. [15][16][17] Several studies have attempted to identify risk factors for DFU but did not assess the status of putting moisturizing cream between toes, family support during foot care, and physical activity (exercise) status of the individual as possible risk factors for the development of DFU. [6][7][8][9] Therefore, this study was conducted to determine the effect of these variables on diabetic foot ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the duration of diabetes mellitus [ 10 ], a history of previous amputations or foot ulceration [ 11 ], inadequate glycaemic control [ 12 ], a history of hypertension [ 13 ], hyperlipidaemia [ 13 ], the presence of PAD [ 13 ], a history of peripheral neuropathy [ 14 ], a history of osteomyelitis [ 15 ], and wound severity [ 16 ] are independent risk factors for LEA. Furthermore, old age [ 17 ], a history of smoking [ 18 ], anaemia [ 19 ], an elevated white blood cell count [ 20 ], hypoalbuminemia [ 19 ], and the presence of microvascular [ 15 , 21 ] and macrovascular complications [ 22 , 23 ] are all believed to contribute to these risk factors. Nevertheless, different studies have reported different findings, and the published data identifying such predictors for diabetes-related LEA in Saudi Arabia are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Terlebih lagi, pada luka yang disebabkan oleh 2 (dua) atau lebih patogen (combined infection) dapat memiliki risiko yang lebih besar. Hal ini sesuai dengan penelitian sebelumnya yang menunjukkan bahwa luka dengan combined infection 11,39 kali lebih berisiko mengalami amputasi (Jeong et al, 2018). Penatalaksanaan infeksi membutuhkan pemilihan infection management yang tepat sesuai dengan hasil pemeriksaan diagnostik dan mikroorganisme, seperti kultur eksudat.…”
Section: Hasil Dan Pembahasanunclassified